Increased GDF-15 in chronic male patients with schizophrenia: correlation with body mass index and cognitive impairment - Tianming Guo; Lihua Chen; Wenxi Sun; Haidong Yang; Jin Li; Xiaobin Zhang; Peng Chen (Schizophrenia)
Abstract Growth Differentiation Factor-15 (GDF-15) is a pleiotropic cytokine that plays a significant role in metabolism and inflammation. Elevated serum levels of GDF-15 have been associated with mood disorders. We propose that GDF-15 may potentially influence cognitive impairment and metabolism in male patients with chronic schizophrenia (CS), although there is limited research on this topic. This study compared serum GDF-15 levels in 72 male patients with CS and 85 healthy controls (HC). The severity of psychotic symptoms was assessed using the Positive and Negative Syndrome Scale (PANSS), while cognitive performance was evaluated with the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). The male CS patients performed worse than the healthy controls in both the total score and all subscales of the RBANS. Serum GDF-15 concentrations were significantly higher in the male CS patients compared to the healthy controls. Furthermore, the log-transformed serum GDF-15 concentrations in male CS patients were positively correlated with BMI and negatively correlated with Delayed Memory scores, Immediate Memory, and the total RBANS score. This preliminary study suggests that elevated serum GDF-15 levels in male patients with chronic schizophrenia may play a role in cognitive function and BMI regulation.